A Linear Functional Equation of Third Order Associated with the Fibonacci Numbers - Soon-Mo Jung; Michael Th. Rassias (Abstract and Applied Analysis)
Given a vector space X, we investigate the solutions f:R→X of the linear functional equation of third order fx=pfx-1+qfx-2+rf(x-3), which is strongly associated with a well-known identity for the Fibonacci numbers. Moreover, we prove the Hyers-Ulam stability of that equation.